Pembelajaran Berbasis Keteladanan sebagai Strategi Penguatan Nilai dan Sikap - Rosmiati Ramli; Mardiati M; Nursia, Nursia; Zulbina, Zulbina (Journal of Humanities, Social Sciences, and Education, 2026)
Role-playing-based learning is a strategic approach to strengthening students' values ​​and attitudes amidst the moral challenges of the era of globalization and digitalization. This article aims to comprehensively examine the role of role models in shaping character, discipline, empathy, tolerance, and a positive learning climate through a literature review method. The study employed a qualitative approach by reviewing various scientific sources in the form of national and international journal articles, proceedings, and relevant academic books published in the last ten years. Data analysis was conducted through the stages of collection, classification, reduction, and synthesis of findings. The results of the study indicate that teacher role models directly influence the internalization of student values ​​through the processes of observation, imitation, and habituation. A school culture built on collective role models has been shown to strengthen attitudes of discipline and social awareness. Furthermore, role models are more effective than instructional approaches in fostering empathy and tolerance. Role models also create a safe classroom climate, increase learning motivation, and strengthen the quality of learning interactions. Furthermore, role-playing-based learning functions as both a pedagogical and moral strategy because it integrates academic objectives with character building. This study confirms that role modeling is not only a method for developing attitudes, but also an important foundation for building meaningful education oriented toward holistic human development. These findings are expected to provide a theoretical and practical basis for developing character education in schools.